A zinc thiocyanate second-order nonlinear optical crystal material and its preparation and application
By developing the second-order nonlinear optical crystal material Zn(SCN)2 of zinc thiocyanate, the optical performance is enhanced by using its linear SCN groups, and the limitations of existing materials in optical transparent windows, second harmonic generation effects and phase matching are solved, and the efficient nonlinear optical performance of broadband laser wavelengths is achieved.
Patent Information
- Application Number
- CN202411071190.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-08-06
AI Technical Summary
The existing nonlinear optical crystal materials have limitations in optically transparent windows, second harmonic generation effects and phase matching, and it is difficult to meet the requirements of broadband laser wavelengths.
A second-order nonlinear optical crystal material Zn(SCN)2 of zinc thiocyanate is developed to enhance the optical properties of the material through its linear SCN groups, achieving strong powder frequency multiplication response, appropriate birefringence and large optical band gap.
The material exhibits a strong frequency multiplication effect under 1064nm laser irradiation, and the powder frequency multiplication intensity is about 30 times that of KDP. It can achieve phase matching and exhibit a higher second harmonic generation effect in the range of 600 to 2000nm.
Smart Images

Figure CN119061482B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to a zinc thiocyanate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art
[0002] Nonlinear optical (NLO) crystals are widely used in modern laser science and technology for applications such as doubling laser frequency or creating tunable light sources called optical parametric oscillators (OPOs). Several NLO crystals have been commercialized, including β-BaB2O4 (BBO), LiB3O5 (LBO), KH2PO4 (KDP), KTiOPO4 (KTP), and AgGaS2 (AGS). Unfortunately, these materials can only meet the requirements of specific application wavelengths due to their limited optical transparency window, weak second harmonic generation (SHG) effect, or insufficient phase matching. Therefore, the development of new and efficient nonlinear optical materials that can output broadband laser wavelengths (from ultraviolet (UV) to visible light (Vis), and then to infrared (IR) regions) is of great academic and commercial significance.
[0003] Although the chemical formula of Zn(SCN)2 (CAS No. 557-42-6) is known, there are also Zn(SCN)2 (space group The unit cell parameters are a=7.794(3), b=10.803(3), c=7.709(3), α=113.25(4)°, β=92.79°, γ=104.40(4)°, Z=4, ) was reported. However, no literature reports on zinc thiocyanate nonlinear optical crystal materials have been found so far. Summary of the invention
[0004] The purpose of the present invention is to provide a zinc thiocyanate second-order nonlinear optical crystal material and its preparation and application in order to overcome the defects of the above-mentioned prior art. Its linear SCN group greatly enhances the linear and nonlinear optical properties of zinc thiocyanate. The obtained zinc thiocyanate exhibits a strong powder double frequency response (30×KDP@1064nm), a suitable birefringence (0.164@546nm) and a large optical band gap (4.56eV).
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In the first aspect, the present invention provides a zinc thiocyanate second-order nonlinear optical crystal material, the chemical formula is Zn(SCN)2, the molecular weight is 181.57, belongs to the tetragonal system, and its space group is The unit cell parameters are a=b= α=β=γ=90°, Z=4, the unit cell volume is
[0007] The present invention is crystallized in a non-central space group The isomer Zn(SCN)2 is a new compound. and existing There are two polymorphs with completely different structures.
[0008] Furthermore, the chemical formula of the crystalline material is Zn(SCN)2, the molecular weight is 181.57, it belongs to the tetragonal system, and its space group is The unit cell parameters are α=β=γ=90°, Z=4. Further preferably, the unit cell parameters are α=β=γ=90°, Z=4. Most preferably, the unit cell parameters are α=β=γ=90°, Z=4.
[0009] The crystal structure of zinc thiocyanate of the present invention is as follows Figure 1 As shown. The structure of Zn(SCN)2 is three-dimensional Framework. Zn(SCN)2 has two crystallographically independent zinc atoms (located on the four-fold axis); Zn(1) is coordinated by four N atoms to form a [ZnN4] tetrahedron; while Zn(2) is coordinated by four S atoms to form a [ZnS4] tetrahedron. The [ZnN4] and [ZnS4] tetrahedrons are connected by shared [SCN] to form a three-dimensional framework.
[0010] Furthermore, the optical crystal material is composed of SCN connected with Zn 2+ Form a three-dimensional coordination framework.
[0011] In the second aspect, the present invention provides a method for preparing a zinc thiocyanate second-order nonlinear optical crystal material, firstly mixing a soluble zinc source, a soluble thiocyanate source and water, stirring to obtain a clear transparent solution, volatilizing to obtain colorless transparent needle-shaped crystals, which are the target product. The ratio of the zinc source and the ammonium thiocyanate source and the reaction temperature are key factors in preparing Zn(SCN)2.
[0012] Furthermore, the added amounts of the soluble zinc source and thiocyanate source satisfy: the molar ratio of the Zn element to the S element is between 1:1 and 3:2, and the amount of the zinc source used is equal to or slightly greater than the amount of the thiocyanate source.
[0013] Furthermore, the soluble zinc source is zinc nitrate hexahydrate.
[0014] Furthermore, the thiocyanate source is ammonium thiocyanate.
[0015] Furthermore, the volatilization temperature is 35-45°C.
[0016] Furthermore, the volatilization time is not less than one week.
[0017] According to the hard-soft acid-base theory, thiocyanate is a boundary acid, which can react with Zn through N and S. 2+ Forming coordination bonds, it can also be bonded by S and NH4 + The diversity of these two bonding modes leads to two competitive reactions in the solution after the thiocyanate source and the zinc source are dissolved in deionized water:
[0018] Zn 2+ + 2SCN - = Zn(SCN)2 (1)
[0019] 2NH4 + + Zn 2+ + 4SCN - + 3H2O = (NH4)2Zn(SCN)4·3H2O (2)
[0020] When Zn in solution 2+ When the concentration of SCN is equal to or slightly greater than that of SCN (the ratio between the two is between 3:2 and 1:1), and the solution temperature is high (temperature range is between 35 and 45 °C), S and Zn 2+ The covalent coordination of S is stronger than that of NH4 through hydrogen bonding. + and H2O, and then (1) reaction occurs; when Zn 2+ When the concentration is lower than that of SCN (the ratio between them is between 2:3 and 2:5) and the solution temperature is low (temperature range is between 15 and 25°C), S and Zn 2+ The coordination bond of S is weaker than that of NH4 through hydrogen bonding. + The ratio of reactants and the temperature range used in the present invention are consistent with the situation of reaction (1), so the prepared crystals are pure crystals in the non-central space group. Zn(SCN)2 crystals.
[0021] In a third aspect, the present invention provides an application of a zinc thiocyanate second-order nonlinear optical crystal material in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
[0022] In a fourth aspect, the present invention provides an application of a zinc thiocyanate second-order nonlinear optical crystal material, wherein the optical crystal material is used in a laser frequency converter, outputs 532nm green light under 1064nm laser irradiation, and outputs 300-1000nm laser under 600-2000nm laser irradiation.
[0023] Specifically, Zn(SCN)2 crystal is used as a nonlinear optical crystal material. It outputs a strong 532nm green light under 1064nm laser irradiation, and its powder frequency doubling intensity is about 30 times that of KDP crystal, and can achieve phase matching, which is about 0.2 to 2 times that of BBO in the range of 600 to 800nm, about 15 to 30 times that of KDP in the range of 900 to 1500nm, and about 1.5 to 2 times that of KTP in the range of 1600 to 2000nm.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The present application provides a new nonlinear optical crystal Zn(SCN)2, which has a large frequency doubling effect. Under 1064nm laser irradiation, its size is about 30 times that of the frequency doubling intensity of the KDP crystal, and its birefringence is 0.164 at a wavelength of 546nm. It can also achieve phase matching, which is about 0.2 to 2 times that of BBO in the range of 600 to 800nm, about 15 to 30 times that of KDP in the range of 900 to 1500nm, and about 1.5 to 2 times that of KTP in the range of 1600 to 2000nm. In addition, the crystal material has good optical transmittance in the ultraviolet, visible and near-infrared light range, and its optical band gap is 4.56eV. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.
[0026] (2) The present application also provides a method for preparing the nonlinear optical crystal Zn(SCN)2, which uses a solution evaporation method to grow a colorless Zn(SCN)2 crystal. The method is simple in process, mild in conditions, and can easily grow single crystals with high optical quality and high purity.
[0027] (3) The zinc thiocyanate crystal material of the present invention can be applied to a laser frequency converter, and can be used to output a laser beam as a double frequency harmonic.
[0028] (4) The crystalline material of the present invention has a wide light transmission band, stable physical and chemical properties, and moderate mechanical hardness, and has important application value in optoelectronic fields such as lithography, spectral analysis, precision manufacturing, and environmental monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the crystal structure of zinc thiocyanate;
[0030] Figure 2 This is a crystal photo of zinc thiocyanate;
[0031] Figure 3 The X-ray diffraction pattern of sample 1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder;
[0032] Figure 4 is the UV-Vis-NIR diffuse reflectance spectrum of sample 1#;
[0033] Figure 5 is the infrared spectrum of sample 1#;
[0034] Figure 6 This is the thermogravimetric analysis spectrum of sample 1#;
[0035] Figure 7 This is the birefringence test chart of sample 1#;
[0036] Figure 8 It is the second harmonic signal diagram of sample 1# and KDP sample with size ranging from 105 to 150 μm;
[0037] Fig. 9 This is the second harmonic phase matching diagram of sample 1# in the 1064nm band.
[0038] Fig.10 It is the second harmonic signal diagram of sample 1# and standard samples BBO, KDP and KTP in the range of 105 to 150 μm and laser wavelength of 600 to 2000 nm. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0040] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0041] Embodiment 1:
[0042] Preparation of samples 1# to 8#
[0043] Mix the zinc source, thiocyanate source and water in a certain proportion to form a raw material, place it in a glass beaker and stir it continuously until a clear and transparent solution is obtained. By slowly evaporating at room temperature, colorless and transparent Zn(SCN)2 needle-shaped crystals can be obtained.
[0044] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 1.
[0045] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0046]
[0047] Crystal structure analysis of samples 1# to 8#
[0048] The structure and phase analysis of samples 1# to 8# were carried out using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0049] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure was analyzed using the Olex2 program package; the positions of atoms were determined using the direct method, and the F-based 2 The coordinates of all atoms and anisotropic thermal parameters were refined by full matrix least squares. All atoms were refined using anisotropic displacement parameters, and the absolute structure was checked using PLATON to find no missing symmetry elements.
[0050] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0051] Among them, the single crystal X-ray diffraction results show that samples 1#~8# have the same chemical formula and crystal structure, the chemical formula is Zn(SCN)2, the molecular weight is 181.57, it belongs to the tetragonal system, and its space group is The unit cell parameters are α=β=γ=90°, Z=4.
[0052] Take sample 1# as a typical example, its crystal structure data is α=β=γ=90°,Z=4. Its crystal structure is as follows Figure 1 shown.
[0053] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 8#, the peak positions of each sample are basically the same, and the peak intensities are basically consistent.
[0054] Take sample 1# as a typical example. Figure 2 As shown, according to the crystal structure analyzed by its single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with the diffraction peak position of the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, indicating that the obtained sample has high purity.
[0055] UV-Vis-NIR diffuse reflectance spectroscopy test
[0056] The diffuse reflectance spectrum test of sample 1# was conducted on a LAMBDA 1050+ UV-Vis-NIR spectrometer from PerkinElmer, USA. The results are shown in Figure 3 As shown by Figure 3 The compound has a wide optical transmission range and an optical band gap of 4.56 eV.
[0057] Infrared spectrum test
[0058] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown in Figure 2, it is proved that the crystalline material contains SCN anions. The characteristic peak of the SCN anion group is at 2150cm -1 Place.
[0059] Thermogravimetric testing
[0060] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the thermal decomposition temperature of the compound is 326°C.
[0061] Birefringence test
[0062] The birefringence test of sample 1# was conducted on an Axioscope A1 polarizing microscope equipped with a Berek compensator from Zeiss, Germany, with a light source wavelength of 546nm. The birefringence can be calculated using the formula:
[0063] ΔR(delay)=|n e -n o | × T=Δn × T (3)
[0064] ΔR represents the optical path difference, Δn represents the birefringence, and T is the thickness of the crystal. The test results are as follows Figure 7 As shown, the crystal optical path difference is 2.937 μm, the crystal thickness is 17.909 μm, and the birefringence measurement value is calculated to be 0.164.
[0065] Frequency doubling test experiment and results
[0066] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the control sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are less than 26, 26-50, 50-74, 74-105, 105-150, and 150-200μm, respectively. Observe the trend of the frequency doubling signal intensity changing with the particle size to determine whether phase matching can be achieved. Under the same test conditions, the second harmonic intensity generated by the sample and the KDP sample is compared to obtain the relative size of the sample frequency doubling effect.
[0067] The variable wavelength frequency doubling test experiment of sample 1# is as follows: an adjustable wavelength laser system is used to measure the frequency doubling effect of sample 1# powder in the range of 600 to 2000 nm, where BBO, KDP and KTP samples with a particle size of 105 to 150 μm are used as references.
[0068] The test results show that the compound zinc thiocyanate crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is 30 times that of the control sample KDP crystal (such as Figure 8 ), phase matching can be achieved (such as Fig. 9 ), about 0.2 to 2 times that of BBO in the range of 600 to 800 nm, about 15 to 30 times that of KDP in the range of 900 to 1500 nm, and about 1.5 to 2 times that of KTP in the range of 1600 to 2000 nm (e.g. Fig.10 ).
[0069] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A zinc thiocyanate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is Zn(SCN)2, molecular weight is 181.57, it belongs to the tetragonal system, and its space group is The unit cell parameters are α=β=γ=90°, Z=4, the unit cell volume is 2. The zinc thiocyanate second-order nonlinear optical crystal material according to claim 1, characterized in that: The optical crystal material is composed of SCN connected with Zn 2+ Forming a three-dimensional gem-like coordination framework.
3. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: Firstly, a soluble zinc source, a soluble thiocyanate source and water are mixed, stirred to obtain a clear transparent solution, and evaporated to obtain colorless transparent needle-shaped crystals, which are the target product.
4. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The added amounts of the soluble zinc source and the thiocyanate source satisfy that the molar ratio of the Zn element to the S element is 1:1 to 3:
2.
5. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The soluble zinc source is zinc nitrate hexahydrate.
6. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The thiocyanate source is ammonium thiocyanate.
7. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The volatilization temperature is 35-45°C.
8. The method for preparing a zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The evaporation time is not less than one week.
9. Application of the zinc thiocyanate second-order nonlinear optical crystal material as claimed in claim 1 or 2 in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
10. Use of a zinc thiocyanate second-order nonlinear optical crystal material as claimed in claim 1 or 2, characterized in that: The optical crystal material is used in a laser frequency converter, and outputs 532nm green light under 1064nm laser irradiation, and outputs 300-1000nm laser under 600-2000nm laser irradiation.
Citation Information
Patent Citations
Sulfocyanic-acid-matches type crystal material, preparation method and use thereof
CN1201082A
Bluish wiolet frequency doubling selenocyanate compound and its prepn process
CN1440974A